Dampak Struktur Modal Terhadap Profitabilitas Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Wardani, Fatimah; , Drs. Agus Muqorrobin, M.M (2017)
This study aims to determine the effect of Capital Structure on Profitability. The sample in this study is a company listed on the Indonesia Stock Exchange with the period 2012-2015. Sampling technique in this research is by purposive sampling. Data analysis method used is normality test and multiple linear regression analysis test with t test, F test, and coefficient of determination (R2). In this study the data met for the classical assumption test. From hypothesis test showed that debt to equity ratio and debt to asset ratio have significant influence with t count respectively equal to -2,037 and -2,125. In the F test shows that the jointly variable debt to equity ratio and debt to assets ratio have a significant effect on return on equity. The result of coefficient of determination (R2) equal to 29,8% Keywords: debt to equity ratio, debt to assets ratio, and return on equity